Attending to the affective: Exploring first year students’ emotional experiences at university - Bharuthram, S. (South African Journal of Higher Education, 2018)
This study engaged students at the affective level in order to acquire a better understanding of their emotional experiences at university with the ultimate aim of improving teaching and learning. A qualitative research study was undertaken whereby students wrote about their feelings at that particular moment, on two different occasions in a semester. The data reveals that students used mostly negative descriptors to express their emotions some of which included feelings of self-doubt, alienation, loss of identity and not belonging to the university and their disciplinary community. The feelings expressed by students show that their emotions constitute the very core of their being and are therefore intertwined with the way they perceive their studies and themselves as students and as individuals. Hence, it is argued that emotional factors cannot be disentangled from teaching and learning and that spaces need to therefore be created in the curriculum for the inclusion of the affective domain.